Rasch Analysis of the Q-CHAT in Colombian Toddlers with Autism Spectrum Disorder (2019)
The objective of this study was the validation of the Colombian version of The Quantitative Checklist for Autism in Toddlers (Q-CHAT) by means of the Rasch Rating Scale Model. The Q-CHAT was applied to parents of 100 typically developing toddlers and 40 toddlers and preschoolers with Autism Spectrum Disorder (ASD). The Q-CHAT scores showed some limitations. The questionnaire did not meet the condition of unidimensionality. Two dimensions were detected. The first dimension, with 13 items and 4 response categories (13i-4c), showed good psychometric properties: the items fit the Rasch Rating Scale model, the reliability of persons and items was appropriate, and scores adequately discriminate between children with and without ASD. The second dimension is a measure of traits that are usually associated with ASD, but that have shown validity problems. Thus, it is proposed that dimension 1 of the Q-CHAT (13i-4c) be used as the screening tool for ASD in Colombia. © 2017, Springer Science+Business Media New York.